IDENTIFIKASI KESULITAN SISWA MTs AL-KHAIRAAT PAKULI PADA PEMECAHAN MASALAH MATEMATIKA DALAM BENTUK SOAL CERITA - Bagus; Salsadila Yunita; Nilawati; karmawati karmawati (Koordinat Jurnal MIPA, 2020)
The purpose of this research was to identify students' difficulties in solving math problems in the form of story problems at Madrasah Tsanawiyah Al-Khairaat Pakuli. This study used a qualitative ethnographic design approach. This research was conducted in the odd semester of the 2020/2021 school year. The research subjects consisted of two students from MTs Al-Khairaat Pakuli, namely S1 and S2. Data collection techniques through observation, interviews and documentation. The results of the study state that (1) subject S1 and S2 can identify and write down what is asked and what is known, (2) subject S1 and S2are also able to convert sentences into mathematical models and (3) subject S1 and S2 can use formulas appropriately by eliminating and substituting what is known in the formula. Based on research conducted by researchers, it can be concluded that the ability of MTs students. Al-Khairaat Pakuli in solving problems related to everyday life in the form of story problems The Two Variable Linear Equation System has reached the maximum level through 2 tests, the two students can understand and solve story problems accurately and consistently.